Effect of Various Acaricides on Hatchability of Eggs of Rhipicephalus (Boophilus) microplus. (26th June 2014) - Haque, M.; Jyoti,; Singh, N. K.; Rath, S. S.
Abstract : The effect of commonly used acaricides (amitraz, cypermethrin, deltamethrin, fenvalerate, and flumethrin) on the eggs of Rhipicephalus (Boophilus) microplus collected from Ludhiana, Punjab, was evaluated by egg hatch assay (EHA). The regression graph of probit hatchability and per cent inhibition of hatching (IH%) of eggs was plotted against log values of concentration of various acaricides. All concentrations of flumethrin and amitraz caused complete inhibition of hatching, whereas a hatchability of 31.0 ± 6.1, 40.0 ± 5.2 and 19.3 ± 1.7 % was only recorded at the highest concentration of cypermethrin, deltamethrin, and fenvalerate, respectively. An increase in the concentration of the acaricide showed a significant effect on the IH% of eggs for cypermethrin P < 0.01 and deltamethrin P < 0.05 but was nonsignificant for fenvalerate. The slope of the regression curve of IH% was utilized for the calculation of the dose of various acaricides causing inhibition of hatching for 95% eggs (LC95 ) and the discriminating dose (DD). Results indicated that maximum DD was recorded for fenvalerate (2.136%), followed by cypermethrin (0.214%) and deltamethrin (0.118%). The results of the current study will be helpful in formulating effective control strategies against ticks.